Hi,
The limits change from a variable in k to a variable in L. Then the summation sign is removed using some identity. I don't know how any of these two steps was carried out.
Thanks for any explanations.
Substitute $\displaystyle l = k - 2 \Rightarrow k = l + 2$. $\displaystyle k = 2 \Rightarrow l = 0$ and $\displaystyle k = n \Rightarrow l = n - 2$.
To evaluate the new sum you're expected to recognise that you have a geometric series (the common ratio is r = 0.9) and you're expected to know the formula for the sum of a geometric series.